Kawin Ajum in Jambi: Socio-Legal and Islamic Law Perspectives on Cultural and Religious Heritage - Yuliatin,; Ghina Nabilah Effedi,; M Kamal Fathoni,; Kholil syuaib,; Al Fauzi Rahmat, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
This article analyses the socio-legal and Islamic law perspectives on the “Kawin Ajum” tradition in Seberang Jambi, a marriage custom arranged by parents or families without the prior consent of the prospective bride and groom. The study aims to investigate the underlying reasons for the continuation of this practice and its compatibility with Islamic legal principles. Employing a qualitative method with a juridical-empirical and sociological approach, the research draws on fieldwork conducted in Seberang Jambi City, an area characterised by strong Islamic and Malay cultural heritage. Data were collected through interviews and literature analysis. The study applies the Islamic legal sociology framework as developed by Kyai Munawwir in Tafsir al-Munawwir and the concept of social fiqh grounded in maqāṣid al-sharī‘ah, particularly as interpreted by Maimoen Zubair and Ahmad Warson Munawwir. This study reveals that Kawin Ajum persists due to the desire to protect local lineage, familial familiarity with the prospective in-laws’ background, and cultural conformity across Jambi. From an Islamic legal standpoint, such marriages are considered valid provided they do not violate principles of ijbār, including kafā’ah (compatibility), consent, and absence of conflict. The study underscores the importance of community dialogue and deliberation as essential in maintaining both cultural values and Islamic legal integrity.